2008
DOI: 10.1377/hlthaff.27.4.964
|View full text |Cite
|
Sign up to set email alerts
|

Specialty Care Systems: A Pioneering Vision For Global Health

Abstract: Successful health-sector reform in developing countries is built on sustainable service delivery models that meet reform goals while addressing community needs. When government efforts fall short, innovative private-sector solutions can offer more-efficient alternatives that provide care to impoverished populations. We identify organizations that use elements of a focused care approach to overcome barriers to delivering care in low-resource settings. Using the experience of the Aravind Eye Care System, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…It sells IOLs to 120 countries and has a world market share by size of about 10 %. It sells large volumes to NGOs, such as Christoffel Blinden Mission, and has thus opened up a new market for IOLs for charitable eye-care for the poor (Bhandari et al 2008).…”
Section: Product Innovationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It sells IOLs to 120 countries and has a world market share by size of about 10 %. It sells large volumes to NGOs, such as Christoffel Blinden Mission, and has thus opened up a new market for IOLs for charitable eye-care for the poor (Bhandari et al 2008).…”
Section: Product Innovationsmentioning
confidence: 99%
“…LAICO's consultancy services to replicate parts or the entire AECS model has helped its partner hospitals increase their productivity and decrease their costs (Bhandari et al 2008). …”
Section: How Are Low-cost Specialty Hospital Chains Potentially Disrumentioning
confidence: 99%
“…Many have a system of generating profit from those who can afford to pay so that the poor can be charged less, or not at all. [19] However, these safeguards cannot take into account all the costs incurred in accessing services (e.g., transport and productivity losses are not included). Indeed, a recent study across five locations in India showed that the ratio of indirect:direct out of pocket expenditure for health care was 1:2.…”
Section: Health Financing and ‘Catastrophic Health Expenditure’mentioning
confidence: 99%
“…Evaluation of the efficiency of specialty hospitals becomes difficult due to the vast diversity of hospital types; therefore conclusions on the performance of such hospitals are mixed based on the set up of the institution being studied (58). Most specialty hospitals in the world are within the US, are owned by physicians, and focus on a specific set of procedures.…”
Section: 4: Specialty Surgical Hospitalsmentioning
confidence: 99%